2012
DOI: 10.1002/etc.1999
|View full text |Cite
|
Sign up to set email alerts
|

PCDD/F release during benthic trawler-induced sediment resuspension

Abstract: Benthic trawling can cause the resuspension of large amounts of sediments. Such regular practice in the Grenland fjord system in the south of Norway has the potential to affect the fate, movement, and bioavailability of sediment-associated polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs). A novel mode of exposing passive sampling devices consisting of towing semipermeable membrane devices attached to the trawl net was used to gauge in situ changes in the freely dissolved concentration of PCDD/Fs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…To represent the background concentrations, 4 pooled samples of cod liver from Skagerrak were included. The data come from various projects and monitoring efforts (Saloranta et al ; Naes et al ; Allan et al ; Eek et al ; Allan et al ; Bakke et al ; Bradshaw et al ; for more details see Supplemental Data). The concentrations were assumed to be log‐normally distributed, reflected in the error model (likelihood function) used in the parameter estimation phase.…”
Section: Theory Materials and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To represent the background concentrations, 4 pooled samples of cod liver from Skagerrak were included. The data come from various projects and monitoring efforts (Saloranta et al ; Naes et al ; Allan et al ; Eek et al ; Allan et al ; Bakke et al ; Bradshaw et al ; for more details see Supplemental Data). The concentrations were assumed to be log‐normally distributed, reflected in the error model (likelihood function) used in the parameter estimation phase.…”
Section: Theory Materials and Methodsmentioning
confidence: 99%
“…First, the spatial division of the fjords (i.e., the structure) is further increased in resolution, to improve the similarity of the model with the real system and to better represent areas that have been identified for possible large‐scale capping. Second, to calibrate the model and estimate model parameters, we now include newer data from biota, sediment, and water samples taken from the recent monitoring efforts (e.g., Bakke et al ) and projects in the Grenland fjords (Cornelissen et al ; Allan et al ; Allan et al ; Bradshaw et al ; Cornelissen et al ). Third, we include the uncertainty surrounding the effect of a relevant and proposed remediation action, namely, capping parts of the polluted fjords with cleaner sediments infused with active carbon (Schaanning and Allan ; Josefsson et al ).…”
Section: Introductionmentioning
confidence: 99%
“…Remobilization of sediment-associated contaminants can occur during natural events, such as tidal movement, floods, and storms, or during human activities such as boat traffic (Superville et al, 2014), dredging, dredge disposal (OSPAR, 2004), and trawling (Allan et al, 2012;Bradshaw et al, 2012). Metal remobilization experiments have been designed for assessing the effects of resuspension (Acquavita et al, 2012;Bataillard et al, 2014;Hamzeh et al, 2014).…”
Section: Changes Of Contaminant Bioavailability During Sediment Distumentioning
confidence: 99%
“…Metal remobilization experiments have been designed for assessing the effects of resuspension (Acquavita et al, 2012;Bataillard et al, 2014;Hamzeh et al, 2014). Field studies using passive sampling devices have also been carried out (Allan et al, 2012;Bradshaw et al, 2012;Superville et al, 2014). The results indicated that metals (in decreasing order: Cd, Ni, Pb, Cu, Zn, Cr) are released rapidly from freshwater sediment with a sharp peak at the beginning of the experiment, followed by a fast coprecipitation and/or adsorption processes on the suspended particles (Hamzeh et al, 2014).…”
Section: Changes Of Contaminant Bioavailability During Sediment Distumentioning
confidence: 99%
“…PSMs measuring C free are used in these assessments in Norway (Bakke et al 2010;Saloranta et al 2011). Other PSM applications relevant to these guidelines are in situ or ex situ measurements of sedimentsurface water fluxes from benthic chambers or box cores (Eek et al 2010) and the case study example given later (Allan, Nilsson et al 2012;Allan, Ruus, et al 2012).…”
Section: Example: Us State-californiamentioning
confidence: 99%